The effect of music on weight gain of preterm infants older than 32 weeks: a randomized clinical trial - Flávia Maria L. Auto; Olga Maria S. Amancio; Fernanda de Córdoba Lanza (Sociedade de Pediatria de São Paulo, 2015)
Objective: To evaluate the effect of recorded music with multimodal stimulation on the weight gain of preterm infants included in the Kangaroo-Mother Program. Methods: Randomized clinical trial with 61 premature infants, of both sexes, with postconceptional age greater or equal to 32 weeks and at least ten days of life, without detected abnormalities in the visual and hearing systems, and hospitalized in the Kangaroo-Mother Unit. Patients were randomized in two groups: of 31 preterm infants received multimodal stimulation with music daily, for seven days; 30 preterm infants received only multimodal stimulation. The following characteristics were evaluated: weight gain, energy consumption, heart rate and respiratory rate, stress signs and feeding method. Comparison between groups was made by Student's t-test, Mann Whitney test and chi-square test, being significant p<0.05. Results: The two groups did not present significant differences in relation to the feeding method and energy consumption (p=0.46); however, weight gain was greater in the Experimental Group (p=0.002), which also presented better stability in cardiac and respiratory rates (p<0.001) and a significant reduction of stress signs (p=0.007), compared with the Control Group. Conclusions: The recorded music with multimodal stimulation is associated with a greater gain in body weight of hospitalized preterm infants as well as presents a positive influence on vital and stress signs (Clinical Trials Registry - UTN: U1111-1153-9301).